IMPROVED PROPELLER EFFICIENCY OF A FERRY SHIP WITH ASYMMETRIC PRE-SWIRL STATOR - Muhammad, Andi Haris; Nikmatullah, Muhammad Iqbal; Kalsum AL, Ummi (Journal of Marine-Earth Science and Technology, 2021)
The International Maritime Organization (IMO) has introduced the importance of the Energy Efficiency Design Index (EEDI) to anticipate global warming and depletion of fuel oil through the development of an Energy Saving Device (ESD) in ship propulsion systems. Pre-swirl stator is a type of ESD installed in front of the propeller which aims to increase propulsion efficiency by reducing the loss of rotational energy in the propeller flow. The purpose of this study is to determine the effect of the 4 blades pre-swirl asymmetric stator diameter on the improved propeller efficiency of KMP Bontoharu using the Computation Fluid Dynamics (CFD) software (Ansys-CFX 18.1). The results showed that the use of a pre-swirl stator on the propeller of KMP Bontoharu could increase the propeller efficiency by 6.64% at a stator diameter of 1.1 DP.